Possible Directions for Improving Consumer Dispute Resolution Mechanisms - Ghukasyan, Shushanik (Bulletin of Yerevan University C: Jurisprudence, 2022)
The article presents the main mechanisms for consumer dispute resolution, highlights the features of considering consumer disputes by courts and ombudsmen, as well as the features of considering such disputes within the framework of alternative dispute resolution mechanisms. The problems arising as a result of the consideration of consumer disputes in the framework of ordinary litigation, the main reasons for filing a small number of claims in courts by consumers were presented, the need to consider such disputes in a special judicial procedure, as well as the need to provide special rules for the consideration of such disputes in the event of their separation in special litigation were justified.